Kajian Hadis tentang Perintah Shalat dan Pendidikan Seks bagi Anak - Syaroji, Syaroji; Amalia, Milda (Intelektualita: Journal of Education Sciences and Teacher Training, 2025)
Nowadays, the phenomenon shows that promiscuity is not only engaged in by teenagers, even children whose status is still in elementary school feel how promiscuity is enjoyed. This is a concern for the public, academics, and most importantly parents. Parents feel uneasy when on social media they present photos and even videos of elementary school children who fall into promiscuity and this goes viral freely. One of the consequences of this promiscuity is the lack of religious education, one of which starts from compulsory prayer. Prayer is the initial religious foundation for children. If this is not handled quickly and appropriately, then the concern is that the morals of the nation's successors will be threatened. This article tries to present how the hadith talks about the commandment of prayer and the perspective of sex education for children and its impact on moral education. Keyword: Children, Hadith Commandment of Prayer, Moral Education.